Discovery of 2-Phenylquinoline-4-Carboxylic Acid Derivatives as Novel Histone Deacetylase Inhibitors - Hui, Qian; Zhang, Lihui; Feng, Jinhong; Zhang, Lei (Frontiers in Chemistry, 2022)
Inhibition of histone deacetylases (HDACs) has been extensively studied in the development of anticancer drugs. In discovery of potent HDAC inhibitors with novel structures, 2-substituted phenylquinoline-4-carboxylic acid group was introduced to the cap moiety of HDAC inhibitors. Totally, 30 compounds were synthesized with hydroxamic acid or hydrazide zinc binding groups. In the enzyme inhibitory test, active compound D28 and its analog D29 exhibited significant HDAC3 selectivity against HDAC1, 2, 3 and 6. However, compared with D28, the hydrazide bearing compounds (D29 and D30) with remarkably improved enzyme inhibitory activities did not exhibit significant antiproliferative potency in the in vitro anticancer study. Further K562 cell based mechanistic results revealed that induction of G2/M cell cycle arrest and promotion of apoptosis make important contributions to the anticancer effects of molecule D28. Collectively, a HDAC3 selective inhibitor (D28) with potent in vitro anticancer activity was developed as a lead compound for the treatment of cancer.